Location-Based Distributed Group Key Agreement Scheme for Vehicular Ad Hoc Network. (22nd February 2014) - Wang, Eric Ke; Ye, Yuming; Xu, Xiaofei
With the rapid development of vehicular ad hoc networks (VANETs), security issues are concerned. Among various security measures, secure group key agreement for VANETs attracts more and more attention. Researchers have studied generic group key agreement schemes for a long while; however, most of them are not designed for VANETs. Considering energy-constrained and fast moving features in vehicular ad hoc network, we propose a new location-based distributed group key agreement LDGKA scheme for VANETs. We adopt a hybrid approach in which members in the vehicular ad hoc network form various logic groups in the same region. Within each group, virtual key tree model is employed so that the rekeying operation can be efficiently carried out when members leave or join. It only requires to rebuildO ( log ⁡ ( n ) ) keys when one node leaves or joins. Moreover, we adopt one-way key derivation to rebuild keys in order to reduce communication overhead of distributing new keys. We also design a protocol for establishing the secure temporary channel dynamically for the nodes that are located in different regions.